Effect of radiant heat exposure on structure and mechanical properties of thermal protective fabrics. (22nd April 2021) - Maurya, Anjani K.; Mandal, Sumit; Wheeldon, Dean E.; Schoeller, Jean; Schmid, Michel; Annaheim, Simon; Camenzind, Martin; Fortunato, Giuseppino; Dommann, Alex; Neels, Antonia; Sadeghpour, Amin; Rossi, René M.
Abstract: The heat protective performance of thermal protective fabrics is related to the multiscale structure of the fibrous material and the composite design of a multilayered fabric system. In this study, a molecular interpretation is provided to explain the structural changes within fibers to correlate with the mechanical properties of the outermost layer fabric made up of m-aramid blended with (5–10) % p-aramid upon various radiant heat exposures. An increase in crystallinity due to limited polymer chain movement but no change in lamellar spacing was observed when fabrics were exposed below the glass transition temperature which resulted in no change in mechanical properties. A noticeable increase in lamellar spacing and crystallinity was obtained when the temperature during the heat exposures is in the proximity of 375 °C of the fabric layer due to the fibrillar-to-lamellar transformation. Even though no visible changes were observed by scanning electron microscopy (SEM) in the fabric exposed to the aforementioned thermal conditions, we found that their mechanical properties are compromised due to the structural changes within fibers of the fabrics. Therefore, further use of fabrics could be potentially dangerous for the user. Furthermore, for expoheat exposures where the temperature of the fabrics reaches above the degradation point, thermal decomposition occurs which is noticed by its hard and brittle behavior. The inner layers of both the fabric systems mostly remain intact until the thermal degradation of the outermost layers. This study provides an in-depth understanding of molecular mechanisms of structural changes that are in line with changes in the mechanical properties. The understanding of the structure-mechanical property relationship could serve as basic knowledge for the design and fabrication of high-performance fabrics for various fire environments. Graphical abstract: Description: Schematic of structural changes upon radiant heat exposures of outermost layer consist of fibers made of m-aramid blended with (5–10) % p-aramid. RT: Room temperature; Tg = 260 °C; Tx = 375 °C; Td = 432 °C. Image 1 Highlights: Multiscale structural characterization of thermal protective fabrics are established using small-angle X-rays scattering (SAXS), wide-angle X-ray diffraction (WAXD), and scanning electron microscopy (SEM). Molecular interpretation of structural changes within the fiber is derived upon various radiant heat exposures of the fabrics. Structure-mechanical property correlation is discussed for radiant heat exposed fabrics. Mechanical properties of the fabrics are compromised due to structural modification in nm-Å scale when the temperature reaches in the proximity of 375 °C of the outermost layer of the fabric made up of m-aramid blended with (5–10)% p-aramid. This study supports improving the design and the fabrication process of thermal protective fabrics.